Risk factors of ICD-11 adjustment disorder in the Lithuanian general population exposed to life stressors - Paulina Zelviene; Evaldas Kazlauskas; Andreas Maercker (European Journal of Psychotraumatology, 2020)
Background: A new definition of adjustment disorder symptoms has been included in the 11th edition of the International Classification of Diseases (ICD-11). However, little is known about risk factors of ICD-11 adjustment disorder. Objective: The study aimed to analyse risk factors of adjustment disorder in a sample of the Lithuanian general population exposed to life-stressors. Method: In total, the study included 649 adult participants from the general population with various recent significant life-stressor experiences. ICD-11 adjustment disorder symptoms were measured using the Adjustment Disorder New Module-8 (ADNM-8) scale. Results: The prevalence of the ICD-11 adjustment disorder diagnosis in the sample was 16.5%. Job-related stressors and health-related stressors were significantly associated with adjustment disorder. Other risk factors for adjustment disorder in this study were female gender, greater age, and university education. Conclusions: We conclude that stressor type and demographic characteristics are associated with the risk of developing an adjustment disorder.